2007
DOI: 10.1097/01.ccm.0000291651.12767.52
|View full text |Cite
|
Sign up to set email alerts
|

Patient-initiated device removal in intensive care units: A national prevalence study*

Abstract: Device removal by ICU patients is common, resulting in harm in one fourth of patients and significant resource expenditure. Further examination of patient-, unit-, and practitioner-level variables may help explain variation in rates and provide direction for further targeted interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 36 publications
6
62
0
8
Order By: Relevance
“…Our rate of unplanned extubation (15%) was consistent with rates reported in the literature, which range from 7% to 18%. 1,[3][4][5][6] The percentage of patients in our study who required reintubation (10.3%), however, was low; researchers in other studies [1][2][3][4][5][6][7]11,14,15,28 have reported reintubation rates of 31% to 78%. This finding, in conjunction with the fact that those patients in our study who experienced unplanned extubation had significantly shorter stays in the MICU and fewer ventilator days suggests that most patients who had unplanned extubation were essentially ready to be extubated.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Our rate of unplanned extubation (15%) was consistent with rates reported in the literature, which range from 7% to 18%. 1,[3][4][5][6] The percentage of patients in our study who required reintubation (10.3%), however, was low; researchers in other studies [1][2][3][4][5][6][7]11,14,15,28 have reported reintubation rates of 31% to 78%. This finding, in conjunction with the fact that those patients in our study who experienced unplanned extubation had significantly shorter stays in the MICU and fewer ventilator days suggests that most patients who had unplanned extubation were essentially ready to be extubated.…”
Section: Discussionmentioning
confidence: 65%
“…Agitation and lack of sufficient sedation have repeatedly been identified as factors contributing to unplanned extubation. 3,4,14,15 To address agitation and standardize sedation management practices among patients receiving mechanical ventilation, many institutions have adopted protocols or guidelines for administration of pain and sedation medications. Implementation of these protocols has decreased the variability of the types of medications used, shortened the duration of mechanical ventilation, and decreased length extubation were prospectively collected on all patients consecutively admitted to the MICU who required mechanical ventilation.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provide support that continuous assessment of sedation by Sedline monitor was associated with a decrease in the incidence of oversedation as was seen in S group. Decreasing sedative use in S group appeared safe and was not complicated by any increase in undersedation events as any self-device removal event, or ventilatory asynchrony [15]. All measured emergence times in this study (defined as verbal command responses (eye opening, hand squeezing) tracheal extubation, and orientation (defined as providing correct date of birth)…”
Section: Discussionmentioning
confidence: 99%
“…Plansız ekstübasyon (PE), endotrakeal entübasyon uygulanan kritik hastalarda görülebilen, morbidite ve mortalitesi yüksek bir durumdur (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Yoğun bakımın ve izlenen hastaların özelliklerine ve mekanik ventilasyon süresine göre insidans değişmektedir (%0,3-16) (7,13,14).…”
Section: Introductionunclassified